The Yield Spread and Bond Return Predictability in Expansions and Recessions - Andreasen, Martin M; Engsted, Tom; Møller, Stig V; Sander, Magnus (Review of Financial Studies, 2021)
This paper uncovers that expected excess bond returns display a positive correlation with the slope of the yield curve (i.e., yield spread) in expansions but a negative correlation in recessions. We use a macro-finance term structure model with different market prices of risk in expansions and recessions to show that a very accommodating monetary policy in recessions is a key driver of this switch in return predictability.